Dampak Kebijakan Nonkehutanan pada Deforestasi dan Kemiskinan di Kalimantan Timur: Sebuah Analisis Berbasis Agen - Azis Khan; Anang Budi Gunawan; Alex Smajgl (Institut Pertanian Bogor (IPB University), 2010)
This paper aims to analyze the impact of non-forestry policy, especially energy related macro policy decisions, on poverty and use levels of natural resources. As core indicators, this analysis employs ‘number of households below the poverty line’ and ‘area of deforestation’. Impacts are analyzed in an agent-based simulation model for 6 districts of East Kalimantan, one of the Indonesian natural-resource rich provinces on the Island of Borneo. Simulation results partly suggest that the policy decision of June 2008-politically known as decreasing fuel price-had nearly no impact on deforestation amplifying that the dominating driver of deforestation is large scale logging and mining operations, as well as potentially illegal activities. While, it reduced the number of poor people-those mostly living within and around forest area-by about 5.4%. Due to seasonal income, this policy-related impact is likely to be periodically lower. During the harvest related period, many households are able to lift their income above the poverty line. This seasonal fluctuation in poverty could help optimize public funding by spreading it over longer periods and by pausing direct transfers during such natural periods of poverty reduction. There is no significant implication for forestry or forest management since the model could only deal with small scale forestry.